Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/art.21894
|View full text |Cite
|
Sign up to set email alerts
|

Gene profiling of scleroderma skin reveals robust signatures of disease that are imperfectly reflected in the transcript profiles of explanted fibroblasts

Abstract: Objective. To determine whether biopsy specimens obtained from systemic sclerosis (SSc) lesions show a distinctive gene profile, whether that gene profile is maintained in fibroblasts cultured from SSc skin biopsy specimens, and whether results from tissue obtained from multiple clinical centers can be combined to yield useful observations in this rare disease.Methods. Biopsy samples and passaged fibroblasts were stored in RNAlater solution prior to processing for RNA. RNA from SSc and control skin biopsy spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
126
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 29 publications
(29 reference statements)
15
126
0
Order By: Relevance
“…This seminal observation focused attention on the pivotal role of the fibroblast in the pathogenesis of fibrosis and spawned extensive research into the underlying mechanisms (105). Persistent fibroblast activation in the absence of the fibrotic tissue milieu, confirmed more recently by DNA microarray studies (52,106,107), indicates autonomous, signal-independent alterations in cell function. The SSc phenotype is characterized by enhanced ECM synthesis, constitutive secretion of cytokines and chemokines, and increased expression of cell surface receptors for fibrogenic signaling mediators (60).…”
Section: Figurementioning
confidence: 75%
“…This seminal observation focused attention on the pivotal role of the fibroblast in the pathogenesis of fibrosis and spawned extensive research into the underlying mechanisms (105). Persistent fibroblast activation in the absence of the fibrotic tissue milieu, confirmed more recently by DNA microarray studies (52,106,107), indicates autonomous, signal-independent alterations in cell function. The SSc phenotype is characterized by enhanced ECM synthesis, constitutive secretion of cytokines and chemokines, and increased expression of cell surface receptors for fibrogenic signaling mediators (60).…”
Section: Figurementioning
confidence: 75%
“…Our data are in line with results obtained with other fibrotic tissue: (i) Gene array analyses of scleroderma and lung fibrosis tissue showed increased fibrillin-2 gene expression levels. 39,40 (ii) In pressure-induced kidney fibrosis, an increase of fibrillin-2 expression was shown by immunohistochemistry and western blotting. 41 (iii) In a wound-healing study, using an antibody against both fibrillin isoforms, fibrillin was identified in the wound tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observation that SSc fibroblasts exhibit an elevated ratio of TGF-␤ type I to type II receptors we have established an experimental model that mimicked this condition in control dermal fibroblasts by carefully titrating the dose of adenoviral vector expressing TGF-␤RI (14). We found considerable overlap between the genes elevated in this experimental model and those previously reported to be overexpressed by lesional SSc fibroblasts and in scleroderma biopsies in vivo (21,22). Among such genes were collagens type I, III, and V, fibronectin, proline 4-hydroxylase, CTGF, SPARC, IGFBP-3, and other matrix protein-related genes.…”
mentioning
confidence: 90%